KESADARAN PESERTA DIDIK DALAM MENJAGA LINGKUNGAN DAN KEBERLANJUTAN SDA DI SMP NEGERI 11 BENGKULU TENGAH - Salamah, Salamah; Sangkut Salsabillah, Rizky; Helmi Susilawati, Helmi Susilawati (FAKULTAS TARBIYAH UNIVERSITAS QOMARUDDIN GRESIK - JAWA TIMUR, 2025)
Students' awareness of protecting the environment and sustainability of natural resources (SDA) is an important factor in creating a healthy and sustainable environment. This research aims to analyze the level of awareness of students at SMP Negeri 11 Central Bengkulu regarding the environment and the role of schools in increasing this awareness. The method used is a qualitative descriptive approach with observation, interviews and questionnaires as data collection techniques. The research results show that the majority of students have a fairly good awareness of protecting the environment, but there are still several obstacles such as a lack of supporting facilities and a lack of socialization regarding the sustainability of natural resources. Efforts that can be made include increasing environmental education programs, providing recycling facilities, and implementing school greening programs.